Electrostatic-modulated interfacial polymerization toward ultra-permselective nanofiltration membranes - You, Xinda; Xiao, Ke; Wu, Hong; Li, Yafei; Li, Runlai; Yuan, Jinqiu; Zhang, Runnan; Zhang, Zhiming; Liang, Xu; Shen, Jianliang; Jiang, Zhongyi (iScience, 2021)
Interfacial polymerization (IP) is a platform technology for ultrathin membranes. However, most efforts in regulating the IP process have been focused on short-range H-bond interaction, often leading to low-permselective membranes. Herein, we report an electrostatic-modulated interfacial polymerization (eIP) via supercharged phosphate-rich substrates toward ultra-permselective polyamide membranes. Phytate, a natural strongly charged organophosphate, confers high-density long-range electrostatic attraction to aqueous monomers and affords tunable charge density by flexible metal-organophosphate coordination. The electrostatic attraction spatially enriches amine monomers and temporally decelerates their diffusion into organic phase to be polymerized with acyl chloride monomers, triggering membrane sealing and inhibiting membrane growth, thus generating polyamide membranes with reduced thickness and enhanced cross-linking. The optimized nearly 10-nm-thick and highly cross-linked polyamide membrane displays superior water permeance and ionic selectivity. This eIP approach is applicable to the majority of conventional IP processes and can be extended to fabricate a variety of advanced membranes from polymers, supermolecules, and organic framework materials. [Display omitted] •Electrostatic-modulated interfacial polymerization is proposed for the first time•Electrostatic attraction regulates the spatial-temporal distribution of amine monomers•Monomer regulation leads to reduced thickness and enhanced cross-linking of membrane•Ultrathin and highly cross-linked polyamide membrane displays superior permselectivity Supramolecular Materials; Materials Science; Materials Chemistry; Materials Synthesis; Polymers